Antimicrobial Resistance Pattern of Uropathogenic Escherichia coli and Klebsiella species Isolated in a Tertiary Care Hospital of Sylhet - Rahman, Md Mahbubur; Chowdhury, Osul Ahmed; Hoque, Md Moynul; Hoque, Syed Anwarul; Chowdhury, Sultana Mehnaz Rahman; Rahman, Md Arifur (Medicine Today, 2018)
The rapid emergence of antimicrobial resistance in major uropathogens has created a global threat especially in the developing countries. In Bangladesh, prescribers of different regions generally diagnose microbial infection on clinical judgment and select antimicrobial on empirical basis, which unfavorably affects the sensitivity pattern of microbes. The present study was designed to determine the prevalence of antimicrobial resistance of Escherichia coli and Klebsiella species isolated from patients with UTI in a tertiary care hospital. This was a cross sectional study conducted at Sylhet MAG Osmani Medical College Hospital, Sylhet from 1st January to 31st December 2016. A total of 200 clinically suspected urinary tract infection patients aged 16-85 years were included in this study. The isolated Escherichia coli and Klebsiella species were tested for antimicrobial susceptibility according to the guideline of Clinical and Laboratory Standards Institute (CLSI) 2011 using the modified Kirby- Bauer disc diffusion technique. Out of 107 pus cell positive ( 05/HPF) urine samples, 75 (70.1%) yielded significant bacteriuria of which 49 (65.3%) were Escherichia coli and 9 (12%) were Klebsiella species. The isolated Escherichia coli showed absolutely high resistance to ampicillin and cefuroxime (100%), moderately high resistance to ceftazidime (81.6%), ciprofloxacin (77.6%), cotrimoxazole (75.5%), cefotaxime (67.4%) and ceftriaxone (59.2%), moderate rate of resistance to amikacin 48.9% and imipenem 46.9% and least rate of resistance to gentamicin (22.5%), nitrofurantion (22.5%) and netilmicin (6.1%). In addition, Klebsiella species revealed completely resistance to ampicillin, cotrimoxazole, cefuroxime, cefotaxime, ceftriaxone, ceftazidime (100%), moderately high resistance to imipenem (88.9%), nitrofurantoin (77.8%), moderate resistance to ciprofloxacin (44.4%), amikacin (33.3%) and gentamicin (33.3%) and least resistance to netilmicin (11.1%). Hence very high resistance rates of 1st line drugs found in uropathigenic Escherichia coli & Klebsiella species, it is necessary to diagnose clinically followed by culture and sensitivity testing. Regular antibiotic surveillance of a particular geographical area is required to establish reliable information regarding susceptibility pattern of uropathogens in order to preserve the continued usefulness of most antimicrobial agents. Medicine Today 2018 Vol.30(2): 61-66